Study of collaborative PRM business model for sustainability. Issue 7 (2nd October 2017) - Ray, Ankita; Mondal, Sandeep
Abstract : Purpose: Sustainable development comprises three bottom line concepts, i.e. protect environment, improve economic performance, and social performance. Business organization with only profitability as the primary objective may lead to a highly competitive market which mainly focuses on financial performance and pay less attention to environmental and social performance. Companies that adopt the product recovery activities also select economic performance as the prime priority of their business objectives. The purpose of this paper is to give a brief idea about a different kind of business model other than conventional business models. Here, the authors aim to represent collaboration among firms, companies, and players within a closed-loop supply chain (CLSC) to build a leading business model that establishes three basic concepts of sustainability. Design/methodology/approach: From literature the authors identified that the primary objective of establishing a sustainable business model is environmental issues but achieving economic performance and gaining market share increase competition among companies. The authors also identified that increasing financial performance results in the development of a competitive business model. This literature review helps to represent the concept of collaborative business model, its benefit, and its mechanism and also helps to compare it with competitive business model in terms of sustainability. Findings: In case of the collaborative business model, the authors found that collaboration is better than competition to sustain in the market. The authors described the collaborative business model and mechanism of both competitive and collaborative business strategies in a CLSC. The authors gave an idea to adopt some well-known business model and pricing policies for the collaborating firms. The authors presented a comparison between the collaborative and competitive business model and also identified different types of collaborative and completive relationship among the players within a CLSC. Originality/value: Government legislations, e-waste rules, and environmental rules involve original equipment manufacturer (OEM) for taking back its end-of-life (EOL)/end-of-use products. A collaborative business model helps OEM to manage those huge amounts of used products by involving third parties within the supply chain. Here, in this paper the authors represent different collaborative parties and their purpose for collaboration, and also represent a strong belief that collaborative business model is the recent trend for establishing sustainability than competitive business model.